2021
DOI: 10.1038/s41409-021-01410-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for outcome after allogeneic stem cell transplantation in patients with advanced phase CML

Abstract: Allogeneic hematopoietic stem-cell transplantation (HSCT) remains the only curative option for patients with advanced chronic myeloid leukemia (CML). However, outcome is dismal and of short follow-up. The objective of the study was to determine long-term outcome and risk factors in patients with a history of CML Blast Crisis (BC; n = 96) or accelerated phase (n = 51) transplanted between 1990 and 2018. At transplant, patients had a median age of 39 (range 7–76) years and were in ≥CP2 (n = 70), in AP (n = 40) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 35 publications
2
27
1
Order By: Relevance
“…Other adverse prognostic factors include a high EBMT risk score (≥5), 63,65 reduced performance status, 64 low CD34 + cell count in graft, and donor age. 62 Radujkovic et al 64 also reported transplant prior to 2010 was associated with increased non-relapse mortality.…”
Section: A L Loge N Eic H a E Mopoietic Ste M Ce L L Tr A Nspl A N Ta...mentioning
confidence: 99%
See 3 more Smart Citations
“…Other adverse prognostic factors include a high EBMT risk score (≥5), 63,65 reduced performance status, 64 low CD34 + cell count in graft, and donor age. 62 Radujkovic et al 64 also reported transplant prior to 2010 was associated with increased non-relapse mortality.…”
Section: A L Loge N Eic H a E Mopoietic Ste M Ce L L Tr A Nspl A N Ta...mentioning
confidence: 99%
“…Peripheral-blood stem cells are preferred over bone marrow as the stem cell source, with lower non-relapse mortality. 62 Patients who achieve a CP2 or better have a superior outcome compared to those transplanted in frank BP. 63,64 Khoury et al and Radujkovic et al reported a three-year OS of 35%-40% and 51.1%, respectively, for BP-CML in remission compared to 8%-11% and 23.3%, respectively, for patients transplanted with active BP-CML, likely due to a higher rate of relapse in the active BP-CML cohorts.…”
Section: A L Loge N Eic H a E Mopoietic Ste M Ce L L Tr A Nspl A N Ta...mentioning
confidence: 99%
See 2 more Smart Citations
“…17 In the most recent report by Neiderweiser et al, donor age >36 years, BP at AlloSCT, and low CD34þ count were shown to be risk factors for inferior OS. 18 ►Table 2 summarizes the contemporary data on transplant outcomes in CML advanced phase. For patients with CML-BP, the data show definitively that AlloSCT represents the best chance of long-term remission or cure.…”
mentioning
confidence: 99%